2019
DOI: 10.1051/0004-6361/201935890
|View full text |Cite
|
Sign up to set email alerts
|

NAOMI: the adaptive optics system of the Auxiliary Telescopes of the VLTI

Abstract: Context. The tip-tilt stabilisation system of the 1.8 m Auxiliary Telescopes of the Very Large Telescope Interferometer was never dimensioned for robust fringe tracking, except when atmospheric seeing conditions are excellent. Aims. Increasing the level of wavefront correction at the telescopes is expected to improve the coupling into the single-mode fibres of the instruments, and enable robust fringe tracking even in degraded conditions. Methods. We deployed a new adaptive optics module for interferometry (NA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Interferometric LM and N band data were obtained on 2019 July 9 and 11 using the instrument MATISSE (Lopez et al 2014) on the VLTI (Table 1). The Auxiliary Telescopes (ATs) were arranged in medium configuration and the New Adaptive Optics Module for Interferometry (NAOMI; Woillez et al 2019) was used. We simultaneously obtained visibility measurements on six baselines (baseline lengths between B = 30 and 95 m).…”
Section: O B S E Rvat I O N Smentioning
confidence: 99%
“…Interferometric LM and N band data were obtained on 2019 July 9 and 11 using the instrument MATISSE (Lopez et al 2014) on the VLTI (Table 1). The Auxiliary Telescopes (ATs) were arranged in medium configuration and the New Adaptive Optics Module for Interferometry (NAOMI; Woillez et al 2019) was used. We simultaneously obtained visibility measurements on six baselines (baseline lengths between B = 30 and 95 m).…”
Section: O B S E Rvat I O N Smentioning
confidence: 99%
“…Actuator and modal gains are also known to depend on device temperature and can be compensated for with calibrated look-up tables, 16,24 although on-sky tests have shown that modal gains are uncorrelated with the DM housing temperature and are better estimated on-sky in the absence of an internal temperature sensor. 27 The drift of the DM membrane via creep contributes a time-dependent source of WFE to the system. In closed loop, creep is corrected as it arises, so we do not anticipate the need for a creep compensation scheme on the system woofer or the NCPC DM under most conditions.…”
Section: Alpao Shape Creepmentioning
confidence: 99%
“…The seeing, which represents the integrated strength of the turbulence along the line of sight, is the parameter used systematically for any instrument at the VLT to constrain the turbulence conditions, and this quantity can evolve rapidly in a matter of minutes. In addition, the use of adaptive optics (AO) systems at the VLT has expanded significantly in the past 3 years: all VLTI instruments are now AO-fed 2,3 and Unit Telescope 4 is a fully adaptive telescope. 4 In terms of operations, this means that new turbulence parameters have to be considered to ensure that these systems deliver their full performance.…”
Section: Supporting the Night Astronomer In Decision-making At Nightmentioning
confidence: 99%